1985
DOI: 10.1007/bf00258538
|View full text |Cite
|
Sign up to set email alerts
|

Mouth occlusion pressure (P0.1) in acute respiratory failure

Abstract: We studied 20 unselected patients admitted to our Intensive Care Unit (ICU) suffering from acute respiratory failure (ARF), who needed mechanical ventilatory support. In all of them we followed a prospective protocol to investigate the value of mouth occlusion pressure (P0.1) as an indicator for weaning. Fifty-two tests were classified into three groups: a need to be reconnected to mechanical ventilation (MV), stable on intermittent mandatory ventilation (IMV), or spontaneous breathing on a T-tube (TT). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 32 publications
5
23
1
2
Order By: Relevance
“…The increased P0.1 during ARF is in agreement with previous studies [22]. Although P0.1 was larger in FW compared to SW patients, in contrast to other studies [23][24][25], the difference in mean P0.1 between these groups did not achieve statistical significance. Similarly, P0.1/PI,max did not separate the FW and SW patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The increased P0.1 during ARF is in agreement with previous studies [22]. Although P0.1 was larger in FW compared to SW patients, in contrast to other studies [23][24][25], the difference in mean P0.1 between these groups did not achieve statistical significance. Similarly, P0.1/PI,max did not separate the FW and SW patients.…”
Section: Discussionsupporting
confidence: 89%
“…The predictive value of P0.1 to indicate FW or SW has been questioned by others [26], who were only able to separate FW and SW patients by a difference in hypercapnic augmentation of P0.1. Nevertheless, most studies [22][23][24][25] have demonstrated that neuromuscular output is augmented in ARF and FW patients. It should be emphasized that the present study did not address the utility of these measured variables in predicting weaning outcome, but they were used to assess differences in the physiological characteristics between FW patients and those with ARF.…”
Section: Discussionmentioning
confidence: 99%
“…Herrara et al (1985) and Sassoon (1987) have obtained similar results. Herrara et al (1985) reported that the patients with Po ., greater than 4.2 cmH2O failed in weaning.…”
Section: Discussionsupporting
confidence: 56%
“…3,11 We previously found P 0.1 to be a valuable index of respiratory-center output, 12 and it has a high enough sensitivity and specificity to contribute to better guidance of weaning from mechanical ventilation. 13 We devised the CORE index:…”
Section: Introductionmentioning
confidence: 99%